2020
DOI: 10.1177/1420326x20963378
|View full text |Cite
|
Sign up to set email alerts
|

Determination of heavy metals and health risk assessment in indoor dust from different functional areas in Neyshabur, Iran

Abstract: The concentration of 10 potentially toxic heavy metals in indoor dust from homes in Neyshabur was investigated. The concentrations of heavy metals in indoor dust from homes ranged from 28.1 to 190.4 µg g−1 for Cr, 24.7 to 162.2 µg g−1 for Ni, 43.8 to 640.4 µg g−1 for Cu, 13.7 to 5,345.7 µg g−1 for Pb, 135.5 to 1,033.0 µg g−1 for Mn, 105.8 to 2,958.0 µg g−1 for Zn, 6,288.0 to 32759.8 µg g−1 for Fe, 2,916.5 to 37,990.0 µg g−1 for Al, 1.3 to 21.4 µg g−1 for Co and 0.5 to 12.9 µg g−1 for Cd. Results of the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The health risk assessment model recommended by US EPA 19,20 and the exposure factors handbook of Chinese population 45,46 and related research results 47,48 were used to assess the health risk of heavy metals in PM adsorbed by the air purifier in 1 year. Heavy metals enter the human body mainly through the following three ways: ingestion, inhalation and dermal contact, and the effect of these three routes on adults and children are different, as shown in equations (1) ∼ (3) 49 where LADD is the average daily exposure to carcinogenesis, mg/(kg·day); ADD is the daily average exposure of non-carcinogenic, mg/(kg·day); C is the concentration of heavy metals, mg/kg; IR ing is the ingestion rate, 200 mg/day for children and 100 mg/day for adults; IR inh is the inhalation rate, 5 mg/day for children and 20 mg/day for adults; EF is the duration of exposure in 350 days/year; ED is the lifetime duration of exposure, 6 years for children and 24 years for adults; CF is the skin conversion coefficient of 1×10 −6 kg/mg; BW is the weight, 16 kg for children and 62 kg for adults; and AT is the average exposure time of children, 2190 days for non-carcinogenic and 25,550 days for carcinogenic, and exposure time for adults are 8760 days and 25,550 days, respectively. PEF is the emission factor of PM, 1.32×10 9 m 3 /kg; SA is the dermal surface exposure, 1600 cm 2 for children and 4350 cm 2 for adults; ET is the frequency of exposure, 4 h/day; and PC is the factor of dermal penetration (As, Cd, Cr, Cu, Ni, Pb and Zn are 0.0018, 0.001, 0.002, 0.006, 0.0001, 0.000,004 and 0.00,006 cm/h, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The health risk assessment model recommended by US EPA 19,20 and the exposure factors handbook of Chinese population 45,46 and related research results 47,48 were used to assess the health risk of heavy metals in PM adsorbed by the air purifier in 1 year. Heavy metals enter the human body mainly through the following three ways: ingestion, inhalation and dermal contact, and the effect of these three routes on adults and children are different, as shown in equations (1) ∼ (3) 49 where LADD is the average daily exposure to carcinogenesis, mg/(kg·day); ADD is the daily average exposure of non-carcinogenic, mg/(kg·day); C is the concentration of heavy metals, mg/kg; IR ing is the ingestion rate, 200 mg/day for children and 100 mg/day for adults; IR inh is the inhalation rate, 5 mg/day for children and 20 mg/day for adults; EF is the duration of exposure in 350 days/year; ED is the lifetime duration of exposure, 6 years for children and 24 years for adults; CF is the skin conversion coefficient of 1×10 −6 kg/mg; BW is the weight, 16 kg for children and 62 kg for adults; and AT is the average exposure time of children, 2190 days for non-carcinogenic and 25,550 days for carcinogenic, and exposure time for adults are 8760 days and 25,550 days, respectively. PEF is the emission factor of PM, 1.32×10 9 m 3 /kg; SA is the dermal surface exposure, 1600 cm 2 for children and 4350 cm 2 for adults; ET is the frequency of exposure, 4 h/day; and PC is the factor of dermal penetration (As, Cd, Cr, Cu, Ni, Pb and Zn are 0.0018, 0.001, 0.002, 0.006, 0.0001, 0.000,004 and 0.00,006 cm/h, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The health risk assessment model recommended by US EPA 19,20 and the exposure factors handbook of Chinese population 45,46 and related research results 47,48 were used to assess the health risk of heavy metals in PM adsorbed by the air purifier in 1 year. Heavy metals enter the human body mainly through the following three ways: ingestion, inhalation and dermal contact, and the effect of these three routes on adults and children are different, as shown in equations ( 1) ∼ (3) 49 Ingestion :…”
Section: Health Risk Assessment Of Heavy Metalsmentioning
confidence: 99%
“…https://journals.sagepub.com/action/doSearch?target=default&ContribAuthorStored=Naimabadi%2C+Abolfazl Previously, Naimabadi et al. reported the presence of high concentrations of HMs in indoor and outdoor DPs of Neyshabur [ 3 , 23 ]. Similarly, the content of HMs in indoor and outdoor DPs was different; remarkably high concentrations of Zn and Ni in indoor DPs compared to that of outdoor ones were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, these metals accumulate in the tissues and cause several malfunctions and diseases [ 1 , 2 ]. HMs enter the body in several ways, the most common way of entering these compounds is through digestion, then breathing, and finally, the skin [ 3 ] HMs in urban soils may endanger human and animal health by entering the food chain; thus, metals present in soils are harmful to human health [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main body of urban heavy metal pollution research includes urban surface dust [3,4], urban soil [5], green spaces [6,7], and other urban components. The research content covers content analysis, spatial variability, risk assessment [8][9][10][11], and systematic and in-depth research on the temporal and spatial properties of urban heavy metal pollution. Among this research, a study on the hazards of heavy metals in urban dust found that heavy metals in dust pose a greater risk to human health than do heavy metals in urban soil [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%